High intensity shock microcycles: An efficient method for improving VO2max in junior alpine skiers - Breil, F. A.; Weber, S. N.; Koller, S.; Hoppeler, H.; Vogt, M. (14th annual Congress of the European College of Sport Science, Oslo/Norway, June 24-27, 2009, Book of Abstracts, 2009)
Maximal oxygen consumption (VO2max) is often used to predict aerobic endurance capacity. In already-trained soccer players, VO2max can be further improved by performing high-intensity interval training (HIT) sessions twice a week over two months (Helgerud et al., 2001). Alternatively, it seems that VO2max can effectively be increased when HIT sessions are performed once or twice daily within a condensed 10-day shock microcycle (Stolen et al., 2005). Such a concept could be particularly useful for athletes who cannot afford the time for extensive endurance training due to high technical and strength demands of their sport. The aim of our study was to investigate the effect of an 11-day high-intensity shock microcycle on endurance and jump performance in junior alpine skiers. Methods: Six female and sixteen male subjects (age: 17.0 ± 1.1 yr, body mass: 67.3 ± 10.4 kg) were matched and randomly assigned to either a high-intensity interval training group (HIT, N = 13) or a control training group (CON, N = 8). HIT performed 15 HIT-sessions (12 on a cycle ergometer, 3 on an obstacle course) during 11 days. Each session consisted of 4×4 min at 90-95% of the individual maximal heart rate (HRmax), separated by 3-min recovery periods. CON continued their normal mixed training including endurance and strength sessions. Before, 24 hours and seven days after the training period, anthropometric data were gathered and ramp tests to exhaustion on a cycle ergometer were performed to determine HRmax, VO2max, peak power output (PPO) and the first and second ventilatory thresholds (VT1, VT2). At the same time-points, countermovement and squat jumps were performed on a force plate. Results and discussion: Body mass and fat-free mass were reduced in HIT only (-1.0%,-1.1% (P < 0.05), respectively). Seven days postintervention HIT significantly improved VO2max by 6.0% (pre: 53.0 ± 4.6, post: 56.2 ± 5.1 mL•kg-1•min-1; P < 0.01) and PPO by 4.4% (pre: 5.2 ± 0.4, post: 5.5 ± 0.5 W•kg-1; P < 0.01). CON showed slight but nonsignificant improvements in VO2max (+3.0%) and PPO (+2.0%). Power output at VT2 increased in HIT by 9.6% (P < 0.01), but not in CON, whereas jump height was unchanged in both groups. In the HITgroup the described functional improvements were already present but to a lesser extent in the post 24-hours measurements. Our results show that high-intensity interval block training might be a very time efficient way to improve VO2max, PPO, and the power output at VT2 in junior alpine skiers. Accumulated fatigue of such an intense training cycle seems to delay the development of the functional adaptations. Therefore, athletes and coaches should plan rest-days to ensure adequate recovery and maximal training effect.